“It Totally Sucked the Happy out of the Gay”: Coming Out in Rural Newfoundland - Roberts, Brittany F (2020)
The coming out process for lesbian, gay, and bisexual (LGB) individuals has been found to significantly impact psychological well-being. Past research suggests that self-disclosing one’s sexual orientation is a major developmental milestone for sexual minorities that can be hindered by the coming out experience. Individuals who experience positive reactions to coming out have been found to have an increased sense of belonging and self-esteem and less mental health concerns. In contrast, individuals who experience negative reactions to coming out have reported an increase in depressive symptoms, substance abuse, incidents of self-harm, and suicidal behaviours. Past research indicates that negative reactions to coming out can significantly compromise both physical and psychological well-being. The present study explored the coming out experiences and psychological well-being of six LGB individuals from rural locations in Newfoundland. Data collected was analyzed using Interpretive Phenomenological Analysis (Smith, Flowers, & Larkin, 2009) and revealed four themes: (i) Fear of Rejection/Negative Repercussions; (ii) Living a Lie; (iii) Masking the Pain; and (iv) Finding Light in the Darkness. This study contributed to current literature regarding coming out in rural areas. Moreover, it contributed to the limited literature existing on coming out in rural Newfoundland. This study highlighted the many challenges faced by LGB individuals from this rural area and also provided insight into the impact of those challenges on psychological well-being. The implications of the research and considerations for future research are discussed.